ASKIYA – A MASTERPIECE OF UZBEK FOLK ART (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article is about the askiya genre – folklore of Uzbek people. The author provides data about development of this verbal contest, its prominent performers, types of this folk art and several examples, as well as uniqueness of this word game.